2009
DOI: 10.1038/ejhg.2009.152
|View full text |Cite|
|
Sign up to set email alerts
|

The 2q23.1 microdeletion syndrome: clinical and behavioural phenotype

Abstract: Eur J Hum Genet. 2009 Oct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 26 publications
3
77
1
Order By: Relevance
“…One such example is the 2q23.1 deletion syndrome, which has been associated with intellectual disability, seizures, microcephaly, and speech delay. Recently, the minimal region has been fine mapped via deletions as small as 37 kbp to a single gene-MBD5 [1, [52][53][54][55]. This gene has also been discovered to contain both a rare mutation and common variants as well as translocation breakpoints by sequencing studies of ID, epilepsy, and ASD (Figure 2) [52,53].…”
Section: Size Spectrum Of Copy Number Variationmentioning
confidence: 99%
“…One such example is the 2q23.1 deletion syndrome, which has been associated with intellectual disability, seizures, microcephaly, and speech delay. Recently, the minimal region has been fine mapped via deletions as small as 37 kbp to a single gene-MBD5 [1, [52][53][54][55]. This gene has also been discovered to contain both a rare mutation and common variants as well as translocation breakpoints by sequencing studies of ID, epilepsy, and ASD (Figure 2) [52,53].…”
Section: Size Spectrum Of Copy Number Variationmentioning
confidence: 99%
“…Some individuals present with an AS-like phenotype. 59,60 Other microdeletion disorders, especially newer ones detected by CGH may be associated with some features of AS. 61,62 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…2,[5][6][7][8] A search of the Database of Genomic Variants (DGV) indicated a copy number gain detected in one individual from one study of 776 control samples from individuals in Northern Germany collected as part of the PopGen project. 17 The Children's Hospital of Philadelphia structural variation project did not find duplications of this region in 2026 presumably healthy individuals, 2q23.1 microduplication BHY Chung et al confirming that it was rarely observed in presumed healthy populations.…”
Section: Control Populationsmentioning
confidence: 99%
“…[2][3][4][5] Microdeletions of chromosome 2q23.1 are associated with a recently described syndrome characterized by DD, language impairment, stereotypic repetitive movements, microcephaly, growth retardation, seizures, and ataxia, reminiscent of the Angelman or Rett syndromes. [6][7][8] The deleted segments in the patients described to date are of variable size ranging from 250 kb to 5.5 Mb, with a common area of overlap including the MBD5 gene. 8 Duplications of chromosome segments involved in microdeletion syndromes have been reported for several common conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation